“Colcha de retalhos” como ponte para construção da identidade docente: um estudo sobre as narrativas no campo da educação estética - Souza, Juliana Paiva Pereira de (2020)
This study presents as a general objective to understand the written narratives elaborated in the "Patchwork Quilt" as an aesthetic awareness of the subjective experiences that constitute the teaching identity, aiming to contribute to the reflection on the personal and professional formation of the subjects in the Pedagogy course. And, for specific purposes: to reflect on the formative device “Quilt Patchwork” as methodology, epistemology and possibility of aesthetic awareness of subjective experiences in the constitution of teacher identity; to map subjective experiences present in written narratives, which comprise four strategies: the report of three striking scenes in high school, the life line chart, the report of what was liked and disliked, and the choice of words at the end of the “Quilt of Patchwork ”(the film narrative); identify the place of aesthetic awareness in the constitution of teacher identity, present in written narratives; reflect on the limits and possibilities of developing the autonomy and emancipation of the subjects in the elaboration of the "Patchwork" Therefore, we will approach concepts such as autonomy, in Freire (1996) and emancipation, in Adorno (2002), the sensitive and rational relationship in Schiller (2002). In Josso (2006), we find the concepts of pivotal moments and the dimensions articulated to the sensible, constituent factors of being the world, articulating with the concepts of Winnicott (1999) about enabling environments, holding and “good enough mother” that in this paper will assume the educational bias. The study material of this research are the 46 narratives produced through the device "Quilt Patchwork" by students who attended the second semester of the Pedagogy Course, in 2018, participants of the discipline "Organization of Teaching Work", taught by Berkenbrock -Rose. The documentary analysis was used as a procedure for the analysis of the documentation composed by the narratives and the contextual questionnaire produced by the students of the second semester of the Pedagogy course from a university in eastern São Paulo. For data organization we used the Thematic Analysis proposed by Jovchelovitch and Bauer (2002). The interpretation will be in light of the philosophical hermeneutics proposed by Gadamer (2000). This study contributed to the reflection on the processes involved in the education of students of Pedagogy courses. Understanding the work with narratives as a primordial factor in the development of autonomy and emancipation of the subjects.